Research on Freezability of Spermatozoa by Use of Various Concentrations of Glycerol in Mithun (Bos frontalis) Semen Cryopreservation - Baruah, K. K.; Mondal, M.; Dhali, A.; Bora, B.; Mech, A.; Baruah, A.; Perumal, P.; Das, K. C. (International Journal of Bio-resource and Stress Management, 2016)
A study was conducted to investigate the various glycerol concentrations on freezability of mithun semen. The present study was conducted in semen production laboratory, ICAR-NRC on Mithun, Medziphema, Nagaland, India. A total of 20 ejaculates were collected from apparently healthy mithun bulls (n=6) by trans-rectal massage method. These ejaculates were extended with tris–egg yolk-citrate-glycerol diluent (TECG) and 5, 6 and 7% (v/v) glycerol, respectively were used as a cryoprotectant. Extended semen was equilibrated, cryopreserved and stored in liquid nitrogen with standard protocols. Semen quality parameters (SQPs) such as percentage of forward progressive motility, viability (Eosin Nigrosin staining), acrosomal integrity (Giemsa staining) and total morphological abnormality (Eosin Nigrosin staining) were estimated with standard procedure at different stage of preservation and with different concentration of the glycerol. The result revealed that these semen quality parameters were differed non-significantly among the three experimental groups at immediately after final dilution (Stage: 1) and differed significantly (p<0.05) at 4 hrs of equilibration (Stage: 2) and at post thawing stage (Stage: 3) of semen cryopreservation. Further, 5% glycerol treated group has shown significantly (p<0.05) higher values of motility and live with acrosomal integrity and lower value of total morphological abnormality than in 6% or 7% glycerol treated groups. Based on the result, it was concluded that 5% glycerol was best for the TECG diluent for preserving mithun semen in liquid nitrogen.